Sistem Persamaan Linier Aljabar Max-Plus untuk Mengoptimalisasi Waktu Produksi Otok Goreng Khas Madura - Rohani, Suci; Amalia, Rica; Yulianto, Tony; Faisol, Faisol (Zeta - Math Journal, 2018)
Every company has a goal to improve the products produced. But in this case the production process of each company must be faced any problems, one of which is the increasingly competitive level of competition that occurs in fried otok companies, especially Otok Goreng HLM H, which requires to determine the amount of production in order to meet market demand on time and the amount accordingly so that it is expected to increase profits from the factory itself. Optimization of production and scheduling time can be modeled using the linear max-plus time invariant theory in a Discrete Event System (DES) where the activity time is in the form of real numbers. Optimization results of the Otok Goreng HLM H production time with the Invariant Time Max-Plus Linear System method, namely the biggest sub-settlement obtained optimal ordering results for the time of ordering as much as 4 times with the fastest time to start production at 07.00 am to 09.50 am, the consumer those who have ordered Otok Goreng HLM H can take the order at 02.03 pm to 4.53 pm or later.